Pengaruh Metode Eksperimen Terhadap Hasil Belajar Fisika Kelas VIII SMP Negeri 2 Tondano - Yoktan Mangar; Patricia Mardiana Silangen; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2022)
Experimental activities are inseparable in learning physics at school. The purpose of this study was to determine the effect of the experimental method on physics learning outcomes for class VIII students of SMP Negeri 2 Tondano. The method used in this study is an experimental method by presenting treatment to two classes with the same level of ability through the form of learning methods. From the results of the analysis of the data normality test using test statistics on the SPSS program "One Sample Kolmogorov Smirnov Test" version 26, it shows that the samples drawn from the two groups, both from the experimental class and the control class, both come from a normally distributed population. Likewise with the homogeneity test, where both groups showed homogeneous or the same variation. The results of the study indicate that there is a significant effect of the experimental method on learning outcomes of light propagation material in class VIII SMP Negeri 3 Tondano.